Faktor Yang Mempengaruhi Cash Holding Perusahaan Manufaktur Di BEI - Leonita Monica, Merry Susanti, Syanti Dewi (Jurnal Paradigma Akuntansi, 2019)
The aim of this research is to examine the effect of firm size, leverage, profitability, andcapital expenditure on cash holding. The sample on this research is limited on manufacturing companies listed on Indonesia Stock Exchange during the year 2015-2017. The hypothesis was examined by multiple linear regression and using Eviews 9 to process the data. The result of this research are leverage andprofitability have a significant impact on cash holding, while firm size, andcapital expenditure have no significant impact on cash holding.